Direct measurement of spin correlations using magnetostriction - Zapf, V.S.; Correa, V.F.; Sengupta, P.; Batista, C.D.; Tsukamoto, M.; Kawashima, N.; Egan, P.; Pantea, C.; Migliori, A.; Betts, J.B.; Jaime, M.; Paduan-Filho, A.; et al. (American Physical Society, 2008)
Fil: Correa, V.F. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Florida State University; Estados Unidos